Systems of Criminal Procedures in the World (Salam International Academic Journal, 2014)
In every county or society, there are different religious, social, political, economic, cultural, ethics and laws, through which the society is organized and relations among the people of that particular geography are managed. The criminal laws and procedures are one those features of any country or society that manages crimes and trail methods that fulfil the need of that particular society. Meanwhile, among these set criminal laws and procedures there are similarities as well as differences from country to country and in different societies. This article try to find out different systems of criminal procedures around the world that is in practice and describes them in detail.
Keywords: Criminal Trials; Accusatory System; Inquisitorial System; Crime Detection; Criminal Prosecution